Molecular genetics of the developing neuroendocrine hypothalamus. - Szareka, Eva; Cheah , Pike See; Schwartz, Jeff; Thomas, Paul (Elsevier, 2010)
Formation of the mammalian endocrine system and neuroendocrine organs involves complex regulatory networks resulting in a highly specialized cell system able to secrete a diverse array of peptide hormones. The hypothalamus is located in the mediobasal region of the brain and acts as a gateway between the endocrine and nervous systems. From an endocrinology perspective, the parvicellular neurons of the hypothalamus are of particular interest as they function as a control centre for several critical physiological processes including growth, metabolism and reproduction by regulating hormonal signaling from target cognate cell types in the anterior pituitary. Delineating the genetic program that controls hypothalamic development is essential for complete understanding of parvicellular neuronal function and the etiology of congenital disorders that result from hypothalamic-pituitary axis dysfunction. In recent years, studies have shed light on the interactions between signaling molecules and activation of transcription factors that regulate hypothalamic cell fate commitment and terminal differentiation. The aim of this review is to summarize the recent molecular and genetic findings that have advanced our understanding of the emergence of the known important hypophysiotropic signaling molecules in the hypothalamus. We have focused on reviewing the literature that provides evidence of the dependence on expression of specific genes for the normal development and function of the cells that secrete these neuroendocrine factors, as well as studies of the elaboration of the spatial or temporal patterns of changes in gene expression that drive this development.